The impact of birth preparedness and complication readiness (BPCR) on maternal outcomes among postpartum mothers - Salsha Billah Putri Radicha; Devi Arine Kusumawardani (Alma Ata University Press, 2024)
Background: Birth preparedness and complications readiness (BPCR) is a strategy to prevent three late causes of maternal death. Previous study results focused on BPCR intermediate outcomes, such as utilizing healthcare facilities during pregnancy and delivery, rather than maternal outcomes like maternal near miss, morbidity, and mortality. Objectives: This study examined the correlation between BPCR practices and maternal outcomes among postpartum mothers Methods: This cross-sectional research was conducted on postpartum mothers in the working area of the Sumberbaru Primary Health Service, Jember Regency, which was carried out from April to June 2023. A total of 78 postpartum mothers were selected using simple random sampling. The interview instrument was adopted from the BPCR JHPIEGO questionnaire, and maternal outcome observations were made using the MCH book. Data were analyzed using the chi-square test to examine the relationship between BPCR and maternal outcome. The level of statistical significance was set to p-value < 0.05 Results: The results of this study indicated that 69.2% of postpartum mothers had less prepared BPCR practices, and for most postpartum women, 55.1% recovered. There was a relationship between BPCR practices and maternal outcomes among postpartum mothers (p-value<0.05). Postpartum mothers with well-prepared BPCR practices had a 3.48 times higher chance of experiencing a complete recovery in maternal outcomes than those with less prepared BPCR practices. Conclusions: The practice of BPCR in postpartum mothers is in the poor category; most mothers' maternal outcomes are in the fully recovered category. BPCR is an essential factor influencing maternal outcomes, so increasing counseling for mothers and families regarding BPCR is necessary to ensure more optimal maternal outcomes.